The Theory Of Planned Behaviour And The Impact Of Moral Norm - Nurul Adilah Hasbullah; Khairil Faizal Khairi; Muhammad Ridhwan Ab. Aziz (Research Academy of Social Sciences, 2024)
The Theory of Planned Behaviour (TPB) is a powerful approach to measure behavioural intention. Among the elements of this theory are attitude, subjective norm and perceived behavioural control. It has been successfully applied in various fields of studies. An additional element proposed by some studies is moral norm. However, the literature that discusses the factors influencing people to make a donation is very limited especially in corporate waqf. Corporate waqf has been chosen to study as it is a new instrument in waqf system and only few have studied it. Therefore, this study aims to examine the factors influencing people’s intention to contribute in corporate waqf, particularly to the employees of Majlis Agama Islam Wilayah Persekutuan (MAIWP). A set of a questionnaire was constructed in order to measure the validity of the theory towards people’s intention in contributing to corporate waqf. The result of this study found that attitude, subjective norm and perceived behavioural control are significantly related to intention to contribute in corporate waqf among people. Attitude is recorded as the strongest factor compared to other factors. In addition, the set of variables in this study is still able to predict a significant amount of the variance in intention to contribute in corporate waqf even though moral norm is controlled.